Evaluating The Visibility of Building Syrian Refugee Shelters by 3D Printing Technology in Jordan - Akeila, Mohanad; Kuok King Kuok, Kelvin; H. Matthew Wong, N. (International Journal of Engineering and Technology, 2019)
Syrian Refugees in Jordan are placed all over the country. Low income refugees are placed in Jordanian camps that miss the basic living standards such as water, electricity, and stable sheltering system. The weakness of refugee camps come in association to the short execution period of construction. New technologies such as 3D printing are emerging with potential to provide better sheltering solutions; however, these technologies are not yet properly explored for providing sustainable shelters to Syrian refugees in Jordan and therefore, this paper developed to evaluate the efficiency of 3D printing technology in comparison to transitional shelters that is commonly used over Jordanian camp, through developing a 3D printable shelter model that assist in studying the cost, the technical specification, and delivery time of shelter printed by the technology. After the comparison, it was found that the 3D printed shelter achieved lower construction cost, higher durability, and can be executed within the same period of transitional shelters.Â Â